Screening for diabetes using Indian diabetic risk score in the field practice area of tertiary care hospital, Maharashtra - Ashturkar, Madhura D.; Kshirsagar, Maya V.; Majumdar, Ratna T.; Dandekar, Ashlesha A. (International Journal Of Community Medicine And Public Health, 2019)
Background: Globally, people living with diabetes were estimated to be 422 million in year 2014. In India, an estimated 7.8% have diabetes. Early detection and prompt treatment for diabetes is key to achieve sustained control and prevent complications. The Indian diabetic risk score (IDRS) is one of simple screening tool to find the risk for diabetes in the community of filed practice area of teaching hospital. Methods: A community based cross sectional study was conducted in urban and rural field practice area during the period of 1st January to 30th September 2018. As per global health report on diabetes, World Health Organization 2016, prevalence of diabetes in India was found to be 7.8%. Considering allowable error as 20% sample size was 1183 which was rounded up to 1200 with 600 each in urban and rural field practice area. The data was collected with bio- data and IDRS questionnaire which includes age, physical exercise, waist circumference and family history of diabetes. Results: Total 1200 Study participants were included in the study. It was observed that 821 (68.41%) were female participants and 379 (31.59%) were male participants. High risk for diabetes was observed in 329 (27.42%) participants. Among the high-risk participants, 194 (58.96%) were from the urban area and 135 (41.04%) were from the rural area. The association between increasing BMI with high IDRS was observed and found statistically significant. High blood pressure was observed among the participants having high IDRS and findings were statistically significant. Conclusions: This simplified IDRS is cost-effective tool to screen the community on large scale.